Epidemiology of Hematologic Malignancies in Real-World Settings: Findings From the Hemato-Oncology Latin America Observational Registry Study - Tietsche de Moraes Hungria, Vania; Chiattone, Carlos; Pavlovsky, Miguel; Abenoza, Lina M.; Agreda, Gladys P.; Armenta, Jorge; Arrais, Celso; Avendaño Flores, Oscar; Barroso, Fernando; Basquiera, Ana L.; Cao, Carmen; Cugliari, Maria S.; et al. (Journal of global oncology, 2019)
Limited information is available on multiple myeloma (MM), chronic lymphocytic leukemia (CLL), and non-Hodgkin lymphoma (NHL) management in Latin America. The primary objective of the Hemato-Oncology Latin America (HOLA) study was to describe patient characteristics and treatment patterns of Latin American patients with MM, CLL, and NHL. This study was a multicenter, retrospective, medical chart review of patients with MM, CLL, and NHL in Latin America identified between January 1, 2006, and December 31, 2015. Included were adults with at least 1 year of follow-up (except in cases of death within 1 year of diagnosis) treated at 30 oncology hospitals (Argentina, 5; Brazil, 9; Chile, 1; Colombia, 5; Mexico, 6; Panama/Guatemala, 4). Of 5,140 patients, 2,967 (57.7%) had NHL, 1,518 (29.5%) MM, and 655 (12.7%) CLL. Median follow-up was 2.2 years for MM, 3.0 years for CLL, and 2.2 years for NHL, and approximately 26% died during the study observation period. Most patients had at least one comorbidity at diagnosis. The most frequent induction regimen was thalidomide-based chemotherapy for MM and chlorambucil with or without prednisone for CLL. Most patients with NHL had diffuse large B-cell lymphoma (DLBCL; 49.1%) or follicular lymphoma (FL; 19.5%). The majority of patients with DLBCL or FL received rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone. The HOLA study generated an unprecedented level of high-quality, real-world evidence on characteristics and treatment patterns of patients with hematologic malignancies. Regional disparities in patient characteristics may reflect differences in ethnoracial identity and level of access to care. These data provide needed real-world evidence to understand the disease landscape in Latin America and may be used to inform clinical and health policy decision making.